2001
DOI: 10.1159/000049501
|View full text |Cite
|
Sign up to set email alerts
|

IgE and IgG Binding Epitopes on α-Lactalbumin and β-Lactoglobulin in Cow’s Milk Allergy

Abstract: Background: Cow’s milk is one of the most common causes of food allergy in the first years of life. We recently defined IgE and IgG binding epitopes for αs1-casein, a major cow’s milk allergen, and found an association between recognition of certain epitopes and clinical symptoms of cow’s milk allergy (CMA). Since α-lactalbumin (ALA) and β-lactoglobulin (BLG) are suspected to be significant allergens in cow’s milk, we sought to determine the structure of sequential epitopes recognized by IgE antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
200
2
12

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(230 citation statements)
references
References 23 publications
16
200
2
12
Order By: Relevance
“…IgE epitopes of Cyp c 1, a prominent class I food allergen, capable of inducing severe systemic anaphylactic reactions, thus seem to be of the conformational type. In case of other class I food allergens, which frequently elicit life-threatening anaphylactic reactions, such as the major peanut allergens Ara h 1, Ara h 2, and Ara h 3 (32-34), the major shrimp allergen, Pen a 1 (35), and major milk allergens (36,37), it has been reported that IgE-binding primarily occurs to linear epitopes (reviewed in Ref. 12).…”
Section: Discussionmentioning
confidence: 99%
“…IgE epitopes of Cyp c 1, a prominent class I food allergen, capable of inducing severe systemic anaphylactic reactions, thus seem to be of the conformational type. In case of other class I food allergens, which frequently elicit life-threatening anaphylactic reactions, such as the major peanut allergens Ara h 1, Ara h 2, and Ara h 3 (32-34), the major shrimp allergen, Pen a 1 (35), and major milk allergens (36,37), it has been reported that IgE-binding primarily occurs to linear epitopes (reviewed in Ref. 12).…”
Section: Discussionmentioning
confidence: 99%
“…In patients likely to 512 outgrow their allergy, three of these IgE-binding epitopes were detected on β-lg and none on α-la 513 (Järvinen et al, 2001). A proteomics approach in combination with immunoblotting, indicated 514 that all major milk proteins including β-lg were allergens, though no evidence was found for α-la 515 (Natale et al, 2004).…”
Section: Allergenicity Of α-Lactalbumin and β-Lactoglobulin 504mentioning
confidence: 99%
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%